Comparación de la Dosis Absorbida Determinada por Dosimetría Directa con los Parámetros del Tomógrafo Computarizado del HPGDR - Vilema, Erika Magaly Tierra; Morocho, Blanca Fabiola Pumalema; Saavedra, Myrian Cecilia Borja; Cevallos, William Bladimir Cevallos; Lucero, Marina Leonor Bonilla (European Scientific Journal, ESJ, 2019)
This paper focuses on comparing the relationship between the dose of radiation obtained from the dosimeter with the dosimetric quantities of the equipment in single skull tomography in the Provincial General Regional Hospital Riobamba, during the period from February to April 2018. The scan was carried out using the Toshiba TSX-031A 16-helical slice tomograph and a DoseRAE2 direct-reading electronic dosimeter. This was placed 3 centimeters from the patient's nape, and the delivered dose was controlled by the operator's console monitor. The research was conducted with 48 adult patients with an age range of 18 to 60 years. The data was analyzed using RStudio and Microsoft Excel. The Kolmogorov Smirnov test and the Student t test were applied. The results indicated that the average values of the tomograph have an emission of excessive radiation of 0.59 mSv over the reference value according to the European Community and the American College of Radiology; knowing thus the dose to which the patient is irradiated. It is recommended to calibrate the dosimetric parameters of the equipment to avoid an overdose and the biological effects on the patient. El objetivo de la investigación fue comparar la relación existente entre la dosis de radiación obtenida del dosímetro, con las cantidades dosimétricas del equipo en tomografías de cráneo simple en el Hospital Provincial Regional General Docente Riobamba, durante el período de febrero a abril del 2018. Para la exploración se utilizó el tomógrafo Toshiba TSX-031A de 16 cortes helicoidal y un dosímetro electrónico de lectura directa DoseRAE2, a 3 centímetros de la nuca del paciente y se controló la dosis suministrada mediante el monitor de consola del operador. La investigación se realizó con 48 pacientes adultos con un intervalo de edad de 18 a 60 años. Los datos fueron analizados mediante R-Studio y Microsoft Excel. Se aplicó el test de Kolmogorov Smirnov y la prueba de t de Student. Los resultados indicaron que los valores medios del tomógrafo tienen una emisión de radiación excesiva de 0,59 mSv sobre el valor de referencia según la Comunidad Europea y el Colegio Americano de Radiología; conociendo así la dosis a la cual se irradia al paciente. Se recomienda la calibración de los parámetros dosimétricos del equipo para evitar una sobredosis y los efectos biológicos en el paciente.